Антропоморфная фигурка из с. Староверовка на Харьковщине - Аксёнов, В.С.; Хоружая, М.В. (My University, 2008)
V. Aksenov, M. Horujaya. Anthropomorphous figure from Staroverovka (village), Kharkiv region In 1976, near Staroverovka village was found bronze anthropomorphous figure. One side of figure represents a male image, other one — female. Found figure pertain to such-named « freak» («urodets»). The statuette is dated 8-10 century. It was produced by Middle Ages Turkic masters. This figure represents an image of Thengri and his wife Umay — creators of Universe, world, nature and human.